Leitura qualificada de Eco-Imagens: Rachel Carson Center Perspectives - Bruno Vinícius Mützenberg (Esboços)
Resenha de: PARAK, Gisela (Ed.). RCC Perspectives. Eco-Images: Historical Views and Political Strategies. Cidade: RCC Perspectives, 2013, n. 1.